Multibody dynamics of pivot slipper pad thrust bearing in axial piston machines incorporating thermal elastohydrodynamics and mixed lubrication model. (April 2016) - Hashemi, Sohil; Kroker, Andreas; Bobach, Lars; Bartel, Dirk
Abstract: A model for the calculation of multibody dynamics incorporating a transient, three-dimensional, thermal elastohydrodynamic pivot pad contact in swash plate axial piston pumps is presented. The simulation is based on the numerical solution of equations of motion, generalized Reynolds, energy and Fourier heat equations. The equation of motion of the hybrid pivot bearing is derived by Lagrangian formalism and solved in due consideration of friction in the spherical joint and piston-barrel. Mass conserving cavitation, non-Newtonian flow and a mixed friction model with consideration of real-measured surface topologies are implemented. Results for a slipper pad with retain plate are presented. The impact of the retain device on slipper pad friction and temperature are discussed. Abstract : Highlights: A cavitation regime is present at the trailing edge and decreases the load capacity. Velocity distribution leads to one-sided temperature rise caused by fluid friction. The retain device has a significant influence on slipper pad operation and friction. Slipper pad without retain plate operates with higher solid body contact load ratio. Film thickness adaption takes place highly dynamical at pressure transition zones.